Tinjauan Hukum Islam Terhadap Monetisasi Youtube Atas Bagi Hasil Google Adsense : Studi Kasus Pada Channel Youtube "MID Raudlatul Ulum Tlagah Galis Bangkalan" (Jurnal Begawan Hukum (JBH), 2025)
YouTube is the most dominant online video provider site in the United States, even the world, with control of 43% of the market. YouTube has features offered with technological advances in various aspects of user needs. The aim of this research is to determine the mechanism for understanding the implementation and observation of Islamic law regarding YouTube monetization of Google Adsense revenue sharing on the MID Raudlatul Ulum Tlagah Galis Bangkalan YouTube channel. The method in this research is qualitative through observation and interviews. The subjects of this research are teachers and students who act as YouTubers at MID Raudlatul Ulum Galis Bangkalan. The results of this research are that there are currently 10.7 thousand YouTube subscribers running for 4 years. With Adsense, registered content users will display advertisements in it. From the perspective of sharia economic law, there are arguments that allow it and there are those that prohibit it, in terms of activities, including Syirkah Abdan, it is permissible.